Expedição Campina dos Leites: uma construção participativa sob a ótica do jovem morador local - Toricelli, Bruna (Universidade Federal de São Carlos, 2018)
In research around environmental education and conservation, the great challenge for the researcher is the popularization of scientific knowledge and the engagement of people on socio-environmental issues, which requires a contextualized approach and strategies that involve values and social participation. For this, this study resorted to the principles of Action Research together with the Socio-environmental Educommunication and the Verde Perto methodology. The objective was to strengthen the bonds of belonging of young people in a rural neighborhood, located in the surroundings of the Ecological Station of Angatuba, with the place where they live and get them to express their opinions and perceptions by means of a documentary video. The research, of qualitative character, was based on the principles of Critical Environmental Education, since the social actors involved were approached as the original source of knowledge. Through a diagnosis was drawn the profile of the young public of the neighborhood and recognized the initial perceptions of these residents by the region. From this information the other steps were developed, which extended over nine months. In this period, the researcher met periodically with the group of young residents to dialogue, discuss ideas, exchange experiences and knowledge, carrying out various socio-environmental activities with them. These meetings, in addition to motivating the reflection, autonomy and the role of young people, have subsidized the elaboration by the group of the documentary video, which presents socio-environmental, historical and cultural aspects of the neighborhood under the optics of them, this being the main product of this research. The video was released to the entire local community and made available in various social media. In addition, it was accepted in the 9th show of Circuito Tela Verde and will be displayed in various places of the country and the world. In the end, it was possible to conclude that the methodologies employed were essential to strengthen the relationships of the young people with each other and with the place where they live. The participants of this study are expected to remain protagonists of their own history and that this research serves as an inspiration for other similar works, to engaging new social actors in the discussion of socio-environmental problems.
Keywords: Pesquisas de natureza interventiva; Educomunicação; Educação ambiental; Conservação; Jovens; Action research; Educommunication; Environmental education; Conservation; Youngs; CIENCIAS BIOLOGICAS